2016
DOI: 10.1155/2016/5179594
|View full text |Cite
|
Sign up to set email alerts
|

Human Ribosomal Proteins RPeL27, RPeL43, and RPeL41 Are Upregulated in Nasopharyngeal Carcinoma Cell Lines

Abstract: Apart from their canonical role in ribosome biogenesis, there is increasing evidence of ribosomal protein genes' involvement in various cancers. A previous study by us revealed significant differential expression of three ribosomal protein genes (RPeL27, RPeL41, and RPeL43) between cell lines derived from tumor and normal nasopharyngeal epithelium. However, the results therein were based on a semiquantitative assay, thus preliminary in nature. Herein, we provide findings of a deeper analysis of these three gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
(31 reference statements)
1
10
0
Order By: Relevance
“…In summary, our studies reveal the significant downregulation of three 40S RP genes ( eS8, uS4 , and eS31 ) and a 60S RP gene (uL14) in NPC cell lines. Our findings reinforce previous reports [ 25 , 26 ] on the occurrence of dysregulated expression among a subset of ribosomal protein genes in NPC. The differential expression pattern of eS8, uS4 , eS31 , and uL14 is revealed for the first time in the NPC context and, hence, adds to the list of possible NPC-associated RP factors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In summary, our studies reveal the significant downregulation of three 40S RP genes ( eS8, uS4 , and eS31 ) and a 60S RP gene (uL14) in NPC cell lines. Our findings reinforce previous reports [ 25 , 26 ] on the occurrence of dysregulated expression among a subset of ribosomal protein genes in NPC. The differential expression pattern of eS8, uS4 , eS31 , and uL14 is revealed for the first time in the NPC context and, hence, adds to the list of possible NPC-associated RP factors.…”
Section: Discussionsupporting
confidence: 93%
“…These two RP genes were downregulated in tumors of NPC relative to normal controls [ 24 ]. Three other genes ( eL27 , eL41 , and eL43 ) were later proven to be NPC-associated RP factors in cell lines derived from NPC tissues [ 25 , 26 ]. However, the hypothesis of eS26 and eS27 as NPC-associated RP genes was subsequently refuted [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Perturbations of several individual RPs have been found in numerous human cancers, including those of the breast, pancreas, bladder, brain and many other tissues [ 13 25 ]. Mutations and deletions of RP-encoding genes have also been found in endometrial cancer, colorectal cancer, glioma, and various hematopoietic malignancies [ 26 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been revealed that certain RPs are expressed in tissue-specific patterns and can differentially contribute to ribosome composition, affect ribosomal RNA processing and regulate translation ( 10 ). Previous studies have reported that perturbations of several individual RPs occur in numerous types of human cancer, including cancer of the brain, pancreas, bladder and other tissues ( 11 17 ). These studies have rapidly established mutations in RPs as a novel, underexplored class of oncogenic factors.…”
Section: Introductionmentioning
confidence: 99%